Air pollution levels in Pasir Gudang commercial, residential, and industrial areas - Mohd. Yusof, Mohd. Badruddin (2006)
The AQI focuses on health effects you may experience within a few hours or days after breathing unhealthy air. The AQI is calculated for four major air pollutants regulated by the Clean Air Act: ground level ozone, particle pollution, carbon monoxide, and sulfur dioxide.